Changes to objective structured clinical examinations (OSCE) at Australian medical schools in response to the COVID-19 pandemic. (3rd April 2022) - Heal, C.; D'Souza, K.; Hall, L.; Smith, J.; Jones, K.; ,
Abstract: Introduction: Objective Structured Clinical Examinations (OSCE) are used to assess clinical skills. We investigated how exit OSCEs changed in Australian medical schools in response to the COVID-19 pandemic. Materials and Methods: The lead ACCLAiM assessment academic from 12 eligible Australian medical school members of the Australian Collaboration for Clinical Assessment in Medicine (ACCLAiM) received a 45-item semi-structured online questionnaire. Results: All schools (12/12) responded. Exit OSCEs were not used by one school in 2019, and 3/11 schools in 2020. Of eight remaining schools, four reduced station numbers and testing time. The minimum OSCE testing time decreased from 64 min in 2019 to 54 min in 2020. Other modifications included: a completely online 'e-OSCE' ( n = 1); hybrid delivery ( n = 4); stations using: videos of patient encounters ( n = 3), telephone calls ( n = 2), skill completion without face-to-face patient encounters ( n = 3). The proportion of stations involving physical examination reduced from 33% to 17%. Fewer examiners were required, and university faculty staff formed a higher proportion of examiners. Conclusions: All schools changed their OSCEs in 2020 in response to COVID-19. Modifications varied from reducing station numbers and changing delivery methods to removing OSCE and complete assessment re-structuring. Several innovative methods of OSCE delivery were implemented to preserve OSCE validity and reliability whilst balancing feasibility.